Low dose MK-801 protects against iron-induced oxidative changes in a rat model of focal epilepsy - YALÇIN, AHMET SUHA; GÜLHAN, REZZAN (My University, 1998)
We have used chemiluminescence measurements to examine the relationship between free radical formation and excitotoxicity in a post-traumatic epilepsy model. For this purpose, seven days after injecting iron in rat brain cortices, we measured luminol- and lucigenin-enhanced chemiluminescence in different brain regions (ipsilateral cortex, contralateral cortex, hypothalamus and hippocampus). In all brain regions (except contralateral cortices) both luminol- and lucigenin-enhanced chemiluminescence were increased in iron-injected group compared to saline-injected control group. These increases returned to control values in iron-injected rats pretreated with MK-801. Our results suggest that both free radicals and excitatory amino acids play important roles in the development of post-traumatic epilepsy and that MK-801 has protective effects against iron-induced chemiluminescence formation.
Keywords: Animals; Rats; Disease Models, Animal; Drug Evaluation, Preclinical; Analysis of Variance; Luminescent Measurements; Electroencephalography; Rats, Sprague-Dawley; Neuroprotective Agents; Dizocilpine Maleate; Epilepsies, Partial; Excitatory Amino Acid Antagonists; Iron